Fused Filament Fabrication‐Based Additive Manufacturing of Commercially Pure Titanium. Issue 12 (23rd September 2021) - Thompson, Yvonne; Polzer, Markus; Gonzalez-Gutierrez, Joamin; Kasian, Olga; Heckl, Johannes P.; Dalbauer, Valentin; Kukla, Christian; Felfer, Peter J.
Abstract : Fabrication of titanium components is very cost intensive, partly due to the complex machining and limited recyclability of waste material. For electrochemical applications, the excellent corrosion resistance of pure titanium is of high importance, whereas medium mechanical strength of fabricated parts is sufficient for such a use case. For smaller parts, metal fused filament fabrication (MF 3 ) enables the fabrication of complex metallic structures densified during a final sintering step. Pure titanium can be processed to near‐net‐shape geometries for electrochemical applications if the parameters and the atmosphere during sintering are carefully monitored. Herein, the influence of thermal debinding and sintering parameters on the fabrication of high‐density pure titanium using MF 3 is investigated. Particular focus is placed on enhancing sintered density while limiting impurity uptake to conserve the high chemical purity of the initial powder material. Relative densities of 95% are repeatedly reached inside the bulk of the samples. An oxygen content of 0.56 wt% as a result of vacuum processing induces the formation of the retained α‐Ti phase (925 HV0.2 ) inside the α matrix (295 HV0.2 ). Fabricated parts exhibit high mechanical strength, albeit reduced elongation due to remaining pores, and, in terms of electrochemistry, enhanced stability toward anodic dissolution. Abstract : The metal fused filament fabrication process is successfully applied for manufacturing of commercially pure titanium. By controlling thermal debinding and sintering parameters, a high sintered density is achieved, while conserving the high chemical purity of the original powder material. The microstructural evolution during processing is shown. Fabricated samples achieve high mechanical strength and increased electrochemical stability toward anodic dissolution.